Characterization of Ouémé River Quality in Upper Delta Using Water Evaluation Indices and Multivariate Analysis - Nireti, Lawani Rebecca Annick; Carine, Kelome Nelly; Micheline, Agassounon Djikpo Tchibozo (European Scientific Journal, ESJ, 2017)
Pollution represents a serious problem for the environment. The aim of this research was to assess the level of organic pollution of the Ouémé River and his physical quality. Nine physical and chemical parameters were measured in nine different stations between March and October 2016, during dry and rainy season. The methods used were those recommended by the French Association of Normalization (AFNOR). Data were subjected to descriptive statistical analysis and multivariate statistical technics, including principal component analysis (PCA) and variance analysis. The Leclercq Organic pollution index was used to assess the level of organic pollution. The values of the measured parameters suggest an organic pollution on all stations. The pollution degree varies according to the study area with contents that sometimes pass those recommended by the WHO standards. More advanced information about water quality for this study area were obtained. Therefore, this study will help stakeholders to better manage Ouémé River’s water.